Vaclovo Biržiškos asmeninės bibliotekos knygos Kauno A. Sniečkaus politechnikos instituto bibliotekoje - Lietuvninkaitė, Nijolė (Knygotyra, 1988)
Vaclovas Biržiška (1884-1956) is a famous Lithuanian bibliographer and researcher of the press. The quantitative and qualitative analysis of the collection of books from Biržiška’s personal library is given in the article. There are 1,480 publications in this collection. 1,072 books are intended for personal purposes. There are books on bibliography, history, pedagogy, and natural science. The collection also includes fiction by Lithuanian, Russian, Western European, American, and Scandinavian writers. The collection is divided into four parts according to language: Lithuanian (495 copies), Russian (520 copies), Polish (304 copies), and other foreign languages (161 copies). The books are marked by Biržiška’s personal ex-libris, designed by P. Galaunė and V. Kosciuška.